Algebra 1

Published by Prentice Hall
ISBN 10: 0133500403
ISBN 13: 978-0-13350-040-0

Chapter 11 - Rational Expressions and Functions - 11-5 Solving Rational Equations - Practice and Problem-Solving Exercises - Page 683: 14


$c=1, 4$

Work Step by Step

Given: $c=c(c-2)-2(c-2)$ $\frac{c}{c}=\frac{c(c-2)}{c}-\frac{2(c-2)}{c}$ $\implies 1=(c-2)-\frac{2(c-2)}{c}$ $\implies 1=(c-2)-\frac{2(c-2)}{c}$ or, $c^2-5c+4=0$ Thus, $(c-4)(c-1)=0 \implies c=1, 4$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.